2018
DOI: 10.3904/kjim.2015.273
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid nodules and their associated clinical parameters: a large-scale, multicenter-based health checkup study

Abstract: Background/AimsWe evaluated the prevalence and characteristics of thyroid nodules detected by thyroid ultrasound (US) at health checkups and the associated clinical parameters.MethodsA total of 72,319 subjects who underwent thyroid US at three health checkup centers in Korea from January 2004 to December 2010 were included in this study. The correlations between the presence of thyroid nodules and other clinical parameters were analyzed.ResultsThe prevalence of thyroid nodules and cysts was 34.2% (n = 24,757).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
86
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 29 publications
15
86
8
2
Order By: Relevance
“…The gender disparity of the presence of TNs was in accordance with previous studies [5,19,20]. Interestingly, this study found a higher odds ratio of TNs (3.36, 95%CI = 1.97-5.75; P < 0.001) in females than previous studies, which indicates a potentially increasing trend of gender disparity on TNs with aging.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The gender disparity of the presence of TNs was in accordance with previous studies [5,19,20]. Interestingly, this study found a higher odds ratio of TNs (3.36, 95%CI = 1.97-5.75; P < 0.001) in females than previous studies, which indicates a potentially increasing trend of gender disparity on TNs with aging.…”
Section: Discussionsupporting
confidence: 57%
“…To our best knowledge, this is the first study to report prevalence of thyroid nodules among centenarians. According to the previous studies, the prevalence of TNs in senior population was 73.7% in China [5], 54.9% in Korea [19], and 46.2% in Cameroon [20]. The differences in the prevalence may be due to age, gender, race, culture, dietary patterns, and iodine supplements [7,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the role of carbohydrate disorders and insulin resistance has been discussed in the pathogenesis of thyroid nodules formation. Several recent studies demonstrated a higher prevalence of thyroid nodules in patients with metabolic syndrome and reported a correlation between thyroid nodule formation and insulin resistance [23][24][25][26]. In view of these findings we can speculate that the high percentage of metabolic syndrome among patients with PA and controls with EH in our study could contribute to the increased prevalence of multinodular goiter.…”
Section: Discussionsupporting
confidence: 57%
“…Further investigation is necessary. The prevalence of thyroid nodules among the general population has also been well-documented [7]. Nevertheless, to our knowledge, no previous studies have reported the prevalence of thyroid cysts among the general Japanese population in those between 40 and 74 years old.…”
Section: Discussionmentioning
confidence: 90%